Torsed intraabdominal testis mimicking acute appendicitis in a 60 year old male - Khan, Abdul Q.; Hazirah, Priya; Dar, Waseem R.; Thomas, Shaji; Ahmad, Ishaq (International Surgery Journal, 2017)
We present a case of 60-year-old male who came to our emergency room with complaints of severe pain in right lower abdomen. Based on history, clinical examination and investigation, we made a provisional diagnosis of acute appendicitis. We explored the patient and found a torsed intraabdominal testis just below the deep ring. Histopathology of the resected specimen showed gangrenous testis.